2023
DOI: 10.3389/fragi.2023.1234958
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelators as a therapeutic option for Alzheimer’s disease—A mini-review

Abstract: Neurodegenerative disorders, particularly Alzheimer’s disease (AD), remain a great challenge regarding the finding of effective treatment, one main reason being the incomplete understanding of their etiology. With many intensely debated hypotheses, a newer approach based on the impact of iron imbalance in sustaining neurodegeneration in the central nervous system becomes increasingly popular. Altered iron homeostasis leads to increased iron accumulation in specific brain areas, explaining the clinical picture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…A recent review involving two iron chelating agents, M30 and HLA20, suggested the neuroprotective role of iron-chelating agents in animal models by reducing neurodegenerative pathology, upregulating signalling pathways that provide neuronal protection, and providing positive behavioural modification [ 37 ]. Several studies have recently proposed the utilisation of iron-chelating agents for the treatment of Alzheimer’s disease [ 62 , 64 ]. Another study used alpha-lipoic acid in transgenic mice models, which prevented tau-hyperphosphorylation and reduced oxidative stress, inflammation, and ferroptosis in neuronal cells [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review involving two iron chelating agents, M30 and HLA20, suggested the neuroprotective role of iron-chelating agents in animal models by reducing neurodegenerative pathology, upregulating signalling pathways that provide neuronal protection, and providing positive behavioural modification [ 37 ]. Several studies have recently proposed the utilisation of iron-chelating agents for the treatment of Alzheimer’s disease [ 62 , 64 ]. Another study used alpha-lipoic acid in transgenic mice models, which prevented tau-hyperphosphorylation and reduced oxidative stress, inflammation, and ferroptosis in neuronal cells [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of aging, iron chelation therapy is a topic of interest due to the potential role of iron accumulation in age-related diseases and conditions. Iron chelating drugs are being explored as a potential therapeutic strategy to manage neurodegenerative diseases and age-related diseases, such as Alzheimer’s disease [ 44 ]. Our results show for the first time that deferoxamine improved M. avium killing in BMMs from old mice in cell culture (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DFO binds iron in a 1:1 ratio and is a hexadentate ligand [ 44 ]. Although being the most popular iron chelator with more than 30 years of clinical experience [ 45 ], DFO application is limited by its short half-life and the need to be administered intravenously or subcutaneously [ 46 ]. Some studies have, however, validated the use of intranasal DFO with the aim of reversing iron-induced memory problems by inhibition of Aβ aggregation, neuronal ferroptosis, τ phosphorylation, and aberrant APP cleavage in AD mouse models [ 47 50 ].…”
Section: Metal Chelators For the Potential Treatment Of Admentioning
confidence: 99%